Hacia un código financiero para el Estado de Quintana Roo - Moreno Cruz, Minerva Maribel (Universidad Michoacana de San Nicolás de Hidalgo, 2014)
The codification activity legally speaking, corresponds exclusively to the legislator, are the lawmakers who take the representativeness of the people are obliged to create laws whose normative assumptions with or are reflection of social reality that exists; Despite them legislators forgetting its commitment of safeguarding the interests of their constituents, have been commissioned to legislate indiscriminately without stopping, the more often to perform a meticulous study of the initiative or project that gets to your consideration and study. Reason why it is frequent to observe inconsistencies, darkness and even omissions in the rules, which make necessary the intervention of the courts for their interpretation and "correction", through the legal criteria or jurisprudence. Our country based on the form of Government, Republican, representative, democratic and federal, integrates States free and sovereign; However, is of all known that sovereignty lies with the Mexican Government as such, and not in the parts that compose it; What exercise Yes States and its municipalities is an autonomy in their internal regime, i.e., in the administration of its Government and public finance. Financial activity, is a set of bodies through which the State meets the needs that are the subject of public services, necessarily linked to a series of rules and areas of knowledge within the public administration; function, which is not unique to the State, but addressing the imperative contained in article 115 of our Constitution, the municipality is responsible for the services that the device itself points out. The State is considered a true economic subject which intervenes in the economy adjusting, planning and controlling directly. It is no longer that the State has some legal instruments to balance the public economy, but have sufficient instruments to balance the economy as a whole, achieve social justice, redistribution of wealth and everything attached to the same State as of its responsibility.

a actividad codificadora jurídicamente hablando, corresponde de manera exclusiva al legislador, son los legisladores quienes al llevar la representatividad del pueblo están obligados a crear leyes cuyos supuestos normativos tengan o sean fiel reflejo de la realidad social que se vive; pese a ellos los legisladores olvidando su compromiso de velar por los intereses de sus representados, se han encargado de legislar indiscriminadamente sin detenerse, las más de las veces a realizar un estudio acucioso de la iniciativa o proyecto que se pone a su consideración y estudio. Razón por la cual es frecuente observar inconsistencia, oscuridad e inclusive omisiones en las normas, que hacen necesaria la intervención de los tribunales para su interpretación y “corrección”, a través de los criterios jurídicos o jurisprudencias. Nuestro país basado en la forma de gobierno, republicano, representativo, democrático y federal, se integra de estados libres y soberanos; sin embargo, es de todos conocidos que la soberanía recae en el Estado Mexicano como tal, y no en cada una de las partes que lo integran; lo que sí ejercen los Estados y sus Municipios es una autonomía en su régimen interior, es decir, en la administración de su gobierno y hacienda pública. La actividad financiera, es un conjunto de órganos mediante los cuales el estado atiende las necesidades que constituyen el objeto de los servicios públicos, necesariamente está ligada una serie de normas y áreas del conocimiento dentro de la administración pública; función, que no es exclusiva del estado, sino atendiendo el imperativo contenido en el artículo 115 de nuestra constitución política, el Municipio tiene a su cargo los servicios que el propio dispositivo señala. El Estado se considera un verdadero sujeto económico que interviene en la economía regulando, planificando y controlando directamente.
Facultad de Derecho y Ciencias Sociales. Maestría en Derecho
Keywords: info:eu-repo/classification/cti/5; FDCS-M-2014-1128; Código financiero; Legislación; Estado; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/578